Girl on fire [compact disc] - Keys, Alicia (RCA : Distributed by Sony Music Entertainment, 2012)
Girl on Fire features an inspirational mix of the rich sounds Alicia Keys discovered while recording and traveling the world, particularly time she spent in London and Jamaica, layered within her New York City roots.